Ecosystem carbon and nitrogen gains following 27 years of grazing management in a semiarid alluvial valley. (1st July 2023) - Morra, Brian; Brisbin, Hondo; Stringham, Tamzen; Sullivan, Benjamin W.
Abstract: Soils in semiarid riparian ecosystems have large carbon (C) stocks that promote water and nutrient availability for productive plant communities consumed by grazing animals. Changes to riparian hydrologic conditions caused by channel incision result in different edaphic conditions and a greater abundance of upland plant species that may be associated with lower soil C stocks. Using riparian meadows alongside Maggie Creek in central Nevada, we show that 27 years of modified grazing practices can repair ecosystem processes and increase the C stocks. We compared C and nitrogen (N) stocks (of soils and plant biomass) on floodplains, terraces, and uplands of reaches where grazing was either modified or excluded to reaches where no changes to grazing practices were made. Grazing management allowed beaver to establish, improving hydrology and lengthening the growing season. These changes allowed C and N to accumulate on geomorphic surfaces that extended from the stream channel to the surrounding hillslopes. A stoichiometric relationship between C and N shows carbon sequestration can reduce nutrient runoff to nearby waterways and may depend on nitrogen availability. Gains in ecosystem carbon ranged from 93 to 452 g C m −2 y −1 and were dominated by increases in soil C. Gains in soil C occurred across the full depth range measured (0–45 cm) and were comparable to those found in restored wetlands and meadows located in more humid ecosystems. Carbon gains exhibited substantial variability caused by microtopography and plant community composition. While grazing exclusion resulted in the largest gains in ecosystem C, managed grazing that limited consumption of riparian plants increased ecosystem C relative to reaches where management wasn't changed. We demonstrate that managed grazing that maintains ecosystem process is compatible with projects aimed at increasing soil carbon in semiarid riparian rangelands. Highlights: Gains in carbon were similar to those found in restored grasslands and wetlands. Significant change in ecosystem carbon occurred in as little as 6–13 years. Gains in carbon and nitrogen occurred together within soils 0–45 cm.